Critical Legal Analysis on Medicine or Vaccine License for Strengthening Access to Justice in Indonesia: A Case of Corona Vaccine Licensing - Agung Sujatmiko; Ghansham Anand; Mochamad Kevin Romadhona (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
This study examines the issue of voluntary licensing for COVID-19 vaccines as a case study to understand the interaction between patent protection, contractual obligations, and accountability mechanisms during a public health emergency. Although the debate on vaccine import and export is no longer central in 2025, analyzing voluntary licensing practices from the pandemic period remains relevant for evaluating the legal and governance frameworks applied at that time. The research focuses on the licensing agreement between PT Bio Farma (Persero) and Sinovac Biotech Co., which played a crucial role in Indonesia’s vaccine procurement and production. The analysis explores how the patent regime regulated under Law Number 13 of 2016 on Patents structured the rights and obligations of the parties, including risk allocation, liability provisions, and the licensor’s responsibilities regarding the safety and performance of the vaccine. Using a statutory and conceptual approach, this study argues that voluntary licensing during the pandemic was not merely a technical mechanism for transferring patent rights, but also a process intertwined with transparency requirements, risk mitigation, and legal protection for the state and end-users. The findings aim to contribute to the body of knowledge on health governance, patent licensing in emergency situations, and the development of more accountable vaccine procurement models for future health crises.